DONEPEZIL HYDROCHLORIDE LOADED SOLID LIPID NANOPARTICLES: FORMULATION, IN VITRO–IN VIVO PHARMACOKINETIC AND PHARMACODYNAMICS EVALUATION - DEVI A., REKHA; M., VIDYAVATHI (International Journal of Applied Pharmaceutics, 2022)
Objective: The aim of the present study was to design and in vitro–in vivo evaluation of Donepezil Hydrochloride solid lipid nanoparticles (DHSLN). Methods: A modified solvent injection method was used to produce Donepezil-loaded solid lipid nanoparticles. A Response Surface Method 3-factor, 2-level Box-Behnken design was applied to study the effect of independent variables on dependent variables. Then it was coated with tween 80 for ease of permeability through the blood-brain barrier due to intact absorption of solid lipid nanoparticles. The prepared SLN was evaluated for particle size, zeta potential analysis, Entrapment efficiency, In vitro drug release study, Field Emission-scanning electron microscopy, In vivo Pharmacokinetic and Pharmacodynamics studies. Results: The results of coated optimized formulation showed an average particle size of 185.8 nm, entrapment efficiency of 78.52±2.54%, and in vitro drug release of 98.62±3.14% at 36h at pH 7.4. The pharmacokinetic data show higher Cmax and improved bioavailability, which was also supported by behavioural changes observed in locomotor activity for surface-modified SLN formulation. Conclusion: Thus, the current study successfully designed, developed an optimized SLN formulation. The surface-modified SLN proved to enhance the permeability of the drug through barrier, which led to the enhancement of Donepezil bioavailability and locomotor activity.